Keterkaitan Kajian Filsafat pada Teori-Teori Belajar dalam Implementasi Kurikulum Merdeka - Nyoman Maesha Bramanda; Desak Putu Parmiti; I Nyoman Jampel; Dewa Bagus Sanjaya (Journal on Education, 2025)
Learning theories have broad implications in various aspects of life. In education, learning theories are used to design curricula, select teaching methods, and evaluate learning outcomes. This paper presents a comparative literature review of three major learning theories: behaviorism, humanism, and cognitivism, in the context of the Merdeka Curriculum. This study analyzed 30 scientific journals published in the last 5 years using thematic analysis to identify key themes and compare the perspectives of the three theories. The results show that behaviorist theory emphasizes observable behavioral changes, while cognitive theory focuses on internal mental processes. Humanistic theory, on the other hand, highlights the importance of intrinsic motivation and a supportive learning environment. The implications of these findings are the importance of combining elements of the three theories in designing effective learning, so that students not only acquire knowledge but also develop critical thinking skills and a positive attitude towards learning. This research makes a significant contribution to our understanding of the relevance of learning theories in the context of the Merdeka Curriculum. By identifying the gap between theory and practice, this research is expected to provide input for the development of a curriculum that is more responsive to student needs and the development of science.